Impact of Bank Specific Factors on Profitability of Nepalese Commercial Banks - Hakuduwal, Kishor (Tribhuvan University Journal, 2021)
This paper aims to investigate the impact of bank specific factors unprofitability of Nepalese commercial banks. Total assets, total deposit, total loan and advance and total equity are taken as independent variables and return on assets is taken as dependent variable. The study is based on pooled least square method. The seven years’ panel data from 2012 to 2018 is taken for the study. Taking 112 observations from sixteen commercial banks, the regression result, F-test and t-test are used for analysis. The study found that the total assets and total loan and advance have positive significant impact on profitability of Nepalese commercial banks. The study also revealed that the total equity has not significant impact and deposit has negative significant impact on profitability of commercial banks in Nepal. The study has important implications for the policy makers of Nepalese commercial banks to utilize their assets, loans, deposits properly and equity for sound profitability.